Economics of cities : theoretical perspectives - Huriot, Jean-Marie, 1945-; Thisse, Jacques-Francois. (Cambridge : Cambridge University Press, 2000)
"Because cities are likely to play an even more predominant role in the global economy in the future than they do at present, it is important to understand how urban centers are created, grow, and function in the process of generating and distributing wealth. This integrated collection of essays exploring the new economic theories concerning cities assembles recent work by a number of the world's leading experts in North America, the United Kingdom and Europe, and Japan. Topics investigated include cities and agglomeration, urban systems, urbanization and growth, and cities and factor markets."--BOOK JACKET.
Includes bibliographical references and index.
Keywords: Urban economics; Cities and towns -- Growth; Economic development; Sociology, Urban